The impact of resistance respiratory muscle training with a SpiroTiger® device on lung function, exercise performance, and health-related quality of life in respiratory diseases - Włodarczyk, Olga M.; Barinow-Wojewódzki, Aleksander (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Introduction : There are studies demonstrating that respiratory muscles can be trained using proper stimulation. Positive effects have been achieved in patients with pulmonary diseases and in patients after thoracic surgery procedures using isocapnic hyperpnoea training with a SpiroTiger ® device. The aim of this study was to investigate whether SpiroTiger ® training has an impact on forced expiratory volume in one second (FEV1), exercise performance, respiratory muscle fitness, and health-related quality of life. Material and methods : Search phrases “spirotiger” and “spiro tiger” were entered into the search engines of the following databases: Academic Search Complete, Medline, Ebscohost, and PubMed. Results : One article about chronic obstructive pulmonary disease (COPD) and 4 articles about cystic fibrosis were found. Conclusions: The positive effect of SpiroTiger ® training on FEV1 cannot be unequivocally confirmed as it was found only in two of the five analysed studies. SpiroTiger ® training has a positive impact on exercise performance measured with the six-minute walk test; it increases breathing muscle fitness in patients with COPD and in patients after thoracic surgery procedures, and it improves health-related quality of life.